Pengaruh penggunaan media wayground terhadap hasil belajar kimia siswa kelas x SMA Negeri 1 Solor Selatan pada materi struktur atom - Herin, Fransiskus Laba; Tiring, Sri Sulystyaningsih Natalia Daeng; Kuki, Agustina Dua (PendIPA Journal of Science Education, 2026)
The study aims to determine the effect of using Wayground media on students’ chemistry learning outcomes on atomic structure material. This research employed a pre-experimental method using a one-group pretest–posttest design. The sample consisted of 30 tenth-grade students of SMA Negeri 1 Solor Selatan. Data were collected through pretest and posttest instruments in the form of multiple-choice questions. Data analysis techniques included normality test, paired sample t-test, and N-gain analysis. The results showed that the average pretest score of 49.33 increased to 85.33 in the posttest. The paired sample t-test revealed a significance value of 0.000 (<0.05), indicating a significant difference before and after the implementation of Wayground media. Furthermore, the N-gain value of 0.72 was categorized as high, demonstrating that Wayground media is effective in improving students’ learning outcomes. Therefore, Wayground can be recommended as an interactive learning medium to enhance students’ motivation, engagement, and understanding of abstract chemistry concepts.